HUBUNGAN FAKTOR INTERNAL MAHASISWA DENGAN PRESTASI BELAJAR: RELATIONSHIP OF INTERNAL STUDENT FACTORS WITH STUDENT ACHIEVEMENTS - Beda, Nikodemus Sili; Salutondok, Dianri Nistia (Bali Medika Jurnal, 2019)
Student success can be seen from the learning achievements taken for some time. Internal factors play an important role in achieving good learning achievement. Based on the data obtained, it can be seen the achievement value> 2.75 and <2.75 are very different. If it is not immediately prevented then it is likely that the number of good learning achievements will decrease. The purpose of this study is to determine the relationship between internal factors of students learning achievement.This research is an analytic observational research with cross sectional study approach. The population of this study was all students of the II level program with a total sample of 66 respondents taken using probability sampling techniques through a systematic random sampling approach. The results of the study used the Chi Square test (Pearson Chi-Sqaure) with a calculated X2 value = 45.438, a value of X2table = 7.815 and also a p value = 0.000 where a value of α = 0.05. this shows that x2count> x2table and p value <α, then Ho is rejected and Ha is accepted. Thus, it can be concluded that there is a relationship between internal factors of students with learning achievement. Therefore it is suggested to students to be more critical in choosing and making decisions related to internal factors so that it does not affect their learning achievement.Keywords: Student Internal Factors, Learning Achievement